SHADOW DETECTION OF AERIAL IMAGES USING SUCCESSIVE THRESHOLDING AND REMOVAL BY ADAPTIVE HISTOGRAM EQUALIZATION - MRS. TRUPTI RAJENDRA GHEWARI; PROF. S. R. KHOT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this paper, the successive thresholding scheme is focus of discussion. In this scheme the modified ratio map obtained by applying the exponential function to the ratio map, is presented to stretch the distance between the ratio values of shadow and non shadow pixels. In order to stumble on the real shadow pixels from the candidate shadow pixels, the connected element system is first implemented to the candidate shadow pixels for grouping the candidate shadow regions. For every candidate shadow area, the local thresholding technique is carried out iteratively to extract the real shadow pixels from the candidate shadow area. Finally, for the remaining candidate shadow regions, a fine-shadow determination process is applied to identify whether each remaining candidate shadow pixel is the true shadow pixel or not.